Efeito do uso de milho rico em lisina na reprodução de galinhas legorne brancas - Aloízio Fonseca , Francisco; Brandão Fonseca, José; Soares, Paulo Rubens; da Silva, Dirceu Jorge (Revista Ceres, 2025)
This experiment was designed to study the effect of opaque-2 com on the reproductive performance of White Leghorn hens. Egg production, egg weight, feed conversion, egg fertility, hatchability of fertile eggs and embryonic mortality were observed.